Problem agenta a przeobrażenia instytucjonalne dotyczące wynagradzania menedżerów zagranicznych i polskich spółek giełdowych - Szapiel, Jolanta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
According to agency theory the incentive contracts should align the interests of corporate managers and shareholders. The purpose of this paper is to test the hypotheses of agency theory in stock market companies. The author tries to prove in particular the effect of institutional changes on the efficiency of managerial compensations which is measured by the value of the corporation's shares and the shareholders gains. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 639-655